Current Height Status and the Discrepancy from Government Growth Targets for 2026 and 2036 Among 9–12-Year-Old Children in Mae Hong Son, Thailand - Mahathamnuchock, Siwaporn (Journal of Population and Social Studies [JPSS], 2025)
Childhood height is a critical indicator of nutritional status and overall health. This cross-sectional study examined factors associated with current and projected future height among school-aged children (9–12 years old) in Mae Hong Son, Thailand. A total of 175 participants were selected from 823 eligible children using systematic sampling across two semi-urban subdistricts. Descriptive statistics summarized sociodemographic and health-related characteristics. One-sample t-tests were used to assess differences between participants’ heights and national reference standards, as well as government target heights for 2026 and 2036. Multiple linear regression identified early childhood development (β = 0.16, p = .039) and sufficient food and nutrition (β = 0.17, p = .022) as significant predictors of current height. Among males, projected height shortfalls ranged from 2.25 to 5.69 cm in 2026 and 7.25 to 10.69 cm in 2036, with most age groups showing statistically significant differences. Among females, the 2026 data showed mixed results, with some age groups exceeding targets, while the 2036 projections revealed consistent shortfalls, with the most significant deficit of -6.69 cm at age 9. These findings reveal age- and gender-specific disparities in meeting national growth targets. Comprehensive, multisectoral interventions addressing nutrition and early childhood development are crucial for enhancing child growth outcomes in rural Thailand.